Technical evaluation of a runway using the deflection method - Yadav, Devinder; Nikraz, Hamid (Vilniaus Gedimino Technikos Universitetas, 2013)
An aircraft imposes a heavy load on a runway during landing, resulting in deflection of the runway pavement. Therefore, runway performance is influenced by potential deflection levels. Estimating deflection at touch-down point is a challenging task, however. Generally, the applied load depends on the weight and vertical velocity of the aircraft before hitting the touchdown point. Similarly, performance of runway pavement is influenced by many factors such as number of landings, load factor, soil characteristics, etc. This study discusses landing practices, imposed load analysis, and runway pavement evaluation. The study is based on the idealisation of runway characteristics using mechanical elements, and it suggests that the mechanical modelling approach can be applied to estimate runway deflection. As a result, the analytically predicted deflection findings instead of the semi-empirical practices currently followed by various states of the International Civil Aviation Organisation (hereinafter - ICAO) can be used to carry out technical evaluation of a runway pavement.